Job Lock in Rural versus Urban Labor Markets. (6th August 2014) - Mushinski, David; Bernasek, Alexandra; Weiler, Stephan
Abstract While the possible negative effect of employer‐sponsored health insurance on labor mobility (job lock) has spawned substantial research, little research has considered differences in job lock between rural and urban areas. Job lock might differ in rural areas because of specific features of rural economies, in particular, the thinness of rural labor markets. This paper estimates measures of job lock for rural and urban areas. Parameter estimates suggest that it is larger in rural areas. The results also indicate that nonwage benefits such as retirement plans, paid vacation, and sick pay are more important factors in married rural workers decisions to change jobs while wages are a more important factor in the transition decisions of single urban workers.